Faktor Penentu Volatilitas Harga Saham pada Perusahaan Sektor Energi di BEI - Sari Puspita Dewi; Nikmah Nikmah (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2025)
This study aims to analyze the effect of exchange rates, interest rates and dividend policies on stock price volatility in energy sector companies listed on the IDX during the 2021-2023 period. The sample was selected using purposive sampling method, consisting of 32 companies. Data analysis was carried out using multiple linear regression. The results showed that exchange rates have a negative effect on stock price volatility, interest rates have a positive effect on stock price volatility, while dividend policy has no effect on stock price volatility. These findings emphasize the importance of considering external factors such as exchange rates and interest rates in making investment decisions in the energy sector.